Evaluation of the Incidence of Anal Fissures in Patients Who Systemic Isotretinoin Therapy for Acne - Hamza Aktaş; Zeynep Şener Bahçe (Mattioli1885, 2023)
Introduction: Isotretinoin is an effective drug widely used in the treatment of severe acne. In this study, we tried to evaluate the incidence of anal fissures with clinical and laboratory side effects associated with isotretinoin. Methods: The study evaluated 210 patients who received systemic isotretinoin treatment. Especially patients with constipation and anal bleeding were evaluated by the General Surgery clinic to arrange appropriate treatments. Results: Of 210 patients included in the study, 138 (65.7%) were female and 72 (34.3%) were male, with a mean age of 23.7 years. The most common adverse event was dry lips in 206 (98.1%) patients. The mucocutaneous side effects were constipation 36 (17.1%), anal bleeding 18 (8.6%), mucosal erosion 10 (4.7%), anal fissure 7 (3.3%). Treatment was discontinued due to elevated liver function tests in 5 patients (2.3%), and because anal bleeding could not be controlled in 1 patient. Conclusions: Isotretinoin is the most effective acne medicine used today. Clarification of the patients about the rarely seen side effects such as dryness, erosion, fissure and bleeding in the anal mucosa in addition to the common mucocutaneous side effects will ensure that patients are more cautious and increase their tolerance to the treatment.